Caracterização de cultivares de bananeira em sistema de cultivo convencional e orgânico - Ribeiro, Lindinéia Rios (2011)
The demand for organic food has been growing worldwide because people are now looking for healthier and environmentally correct food products as well as bigger rentability, but there is no safe literature information to support banana production in the organic system. Based on that, the objective of this study was to compare agronomic and physical-chemical traits in banana production both in conventional and organic management. For this we used the cultivars, Caipira (AAA), Maravilha (AAAB), Ken Pacovan (AAAB), Prata Anã (AAB), Thap Maeo (AAB) and Tropical (AAAB). The conventional management consisted of chemical fertilization without using nor herbicides or pesticides. In the organic management, natural fertilizers (castor-oil and wood ash) and live coverage were used. We evaluated the characters, plant height, pseudostem diameter, number of leaves during flowering and harvest, early, yellow Sigatoka, total weight of the bunch, weight of bunches, number of fruits per bunches, fruit number, length and diameter average fruit weight of fruits with and without bark, fruit diameter and length, bunch weight, number of fruits per bunch and thickness, soluble solids, titratable acidity, ratio (ratio acid / soluble solids), pH, moisture and soluble sugars (reducing, non-reducing and total). Differences have been found both in agronomic and physical and chemical traits, according to the Scott Knott test. The analysis of variance and mean tests used show differences and agronomic characteristic between the physical-chemical farming systems and among cultivars within each system. The organic farming system promoted increase in plant height, number of life leaves during flowering and the length and diameter. Regarding the physical-chemical parameters of fruit was found that the cultivation system and affected moisture content of not reducing sugars and soluble solids. All cultivars showed significant differences within each culture system m for the parameters analyzed.